PENELITIAN BUDAYA HUKUM:KONSEP DAN METODOLOGI - Teddy Asmara (Masalah-Masalah Hukum, 2014)
This paper discusses the coherence between the concepts and methods of the legal culture study according to the ideational approach of anthropological perspective, and operational examples presented through techniques to formulate the problem in qualitative research. By using the emergent design, research problems in the proposal is still tentative and / or open it will be enhanced inductively in the field, through the process of intensification of theoretical sensitivity of the phenomenon. Change research problems and themes as well as the diversity of research methods is as a consequence of the strategy to explore the phenomenon being studied. Techniques so as one of the main ways to obtain the coherence of concepts and methods as well as a definitive study design were further narrated in the research report.